A Cost-Effective Digital Solution for Community Libraries: A TAM Evaluation of a CMS-Based Book Circulation System - Vina Zahrotun Kamila; Eko Subastian; Putut Pamilih Widagdo; Riftika Rizawanti (International Journal of Engineering, Science and Information Technology, 2025)
The digital transformation of community-based libraries in developing regions requires careful consideration of user acceptance factors for successful implementation, particularly when managing physical book collections through online systems. This study evaluates user acceptance of a CMS-based online book circulation system implemented in "Ramah Baca," a community library in East Kalimantan, Indonesia. The system utilizes WordPress CMS with a modified WooCommerce plugin specifically adapted for physical book lending operations. Using the Technology Acceptance Model (TAM), this research examines how Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Behavioral Intention to Use (BI), and Actual Use (AU) influence users' Attitudes Toward Using (ATU) the CMS-based  book circulation system. A quantitative survey of 40 active users revealed that Perceived Usefulness (? = 0.511, p = 0.002) and Behavioral Intention to Use (? = 0.456, p = 0.017) significantly positively affected Attitude Toward Using, while Perceived Ease of Use (p = 0.831) and Actual Use (p = 0.701) showed no significant partial effects. Collectively, all variables significantly influenced Attitude Toward Using (F-value = 24.959, p 0.001). The findings suggest that for community library physical book circulation systems in developing regions, enhancing perceived usefulness and fostering long-term engagement are more critical than focusing primarily on ease of use. The successful adaptation of WordPress and WooCommerce demonstrates the viability of using modified e-commerce platforms for physical book management in resource-constrained environments.